Potential revival of cholinesterase inhibitors as drugs in veterinary medicine - Žnidaršič, Neža; Štrbenc, Malan; Grgurevič, Neža; Snoj, Tomaž (Frontiers in Veterinary Science, 2023)
The cholinergic system is involved in the regulation of all organ systems and has acetylcholine as almost its only neurotransmitter. Any substance is called cholinergic if it can alter the action of acetylcholine. Cholinesterases are enzymes that enable the hydrolysis of acetylcholine and in this way ensure homeostasis in cholinergic synapses. Cholinesterase inhibitors are a group of indirect-acting cholinergic agonists that influence the activity of the cholinergic system. Several compounds that can inhibit cholinesterases are of importance to veterinary medicine from pharmacological and toxicological perspective. The frequency of their use in veterinary medicine has fluctuated over the years and is now reduced to a minimum. They are mainly used in agriculture as pesticides, and some are rarely used as parasiticides for companion animals and livestock. In recent years, interest in the use of new cholinesterase inhibitors has increased since canine cognitive dysfunction (CCD) became a recognized and extensively studied disease. Similar to Alzheimer's disease in humans, CCD can be treated with cholinesterase inhibitors that cross the blood‒brain barrier. In this review, the mammalian cholinergic system and the drugs that interact with cholinesterases are introduced. Cholinesterase inhibitors that can be used for the treatment of CCD are described in detail.